20. CLINICAL AND SUBCLINICAL FEATURES OF NON-ALCOHOLIC FATTY LIVER DISEASE (NAFD) IN PATIENT WITH TYPE 2 DIABETES MELLITUS IN NGHE AN FRIENDSHIP GENERAL HOSPITAL 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: To investigate non-alcoholic fatty liver disease’s clinical and subclinical characteristics in patients with type 2 diabetes from July 2022 to June 2023. Population and methods: Case series description of 262 patients who had type 2 diabetes with nonalcoholic fatty liver disease. Diagnosis of fatty liver by ultrasound. Results: Average age 66.5 ± 10.7; the ratio of men and women is 49.2% and 50.8%. Typical clinical symptoms are fatigue and loss of appetite (99.6% and 96.6%). Common paraclinical indicators include decreased red blood cell count, decreased hemoglobin, increased LDL-C, and increased HDL-C in 34.4%, 75.9%, 71.0%, and 38.9%, respectively. Hemoglobin count, platelet count, and LDL-C index in women were higher than in men, with p
Keywords: Non-alcoholic fatty liver disease; type 2 diabetes; Nghe An genaral Friendship Hospital.